FUZZY LOGISTIC REGRESSION APPLICATION ON PREDICTIONS CORONARY HEART DISEASE - Febriani, Vera; Lestari, Dian; Mardiyati, Sri; Lilyasari, Oktavia (PATTIMURA UNIVERSITY, 2023)
According to the World Health Organization (WHO) in 2015, 70% of cardiac deaths were caused by coronary heart disease (CHD). Based on WHO data in 2017, 17.5 million deaths were recorded, equivalent to 30% of the total deaths in the world caused by coronary heart disease. Coronary heart disease is a disorder of heart function caused by plaque that accumulates in arterial blood vessels so that it interferes with the supply of oxygen to the heart tissue. This causes reduced blood flow to the heart muscle and oxygen deficiency occurs. In more serious circumstances, it can result in a heart attack. Risk factors for coronary heart disease include age, gender, hypertension, cholesterol, heredity, diabetes mellitus, obesity, dyslipidemia, smoking and lack of physical activity. If a person's chances of suffering from coronary heart disease can be predicted early based on the existing risk factors, then the mortality rate of coronary heart disease can be suppressed. The objective of this study is to build a model that can predict the possibility of a patient suffering from coronary heart disease. The study used the Fuzzy Logistic Regression model. This model was used to maximize prediction results in which data size was limited. The least square method was used to estimate the value of the parameter. We obtained from National Cardiovascular Center Harapan Kita, Jakarta. Evaluation with the Mean Degree of Membership method showed that the model built was feasible and good enough to predict coronary heart disease. By using the confusion matrix, the accuracy of the prediction model is 80.00%, with a specificity of 42.85% and a sensitivity of 100%.